Answer:
0
4
15
27
Step-by-step explanation:
a) The first expression is
[tex]50-b^2+a[/tex]
When a=2 and b=5, we get
[tex]50 - {(5)}^{2} + 2 = 50 - 25 + 2 = 27[/tex]
b) The second expression is
[tex]a^2(5-b)[/tex]
We substitute a=2 and b=5;
[tex] {2}^{2} (5 - 5) = 4(5 - 5) = 4 \times 0 = 0[/tex]
c) The next expression is
[tex] {b}^{2} - 10[/tex]
We substitute b=5 to get:
[tex] {5}^{2} - 10 = 25 - 10 = 15[/tex]
d) The fourth expression is
[tex]a(b-3)[/tex]
When a=2 and b=5
[tex]2(5 - 3) = 2 \times 2 = 4[/tex]
We know that:
0<4<15<27